The Effectivity of Porous Hydroxyapatite loaded with Gentamycin on Chronic Tibial Osteomyelitis in Rabbit Models - Ismail Dilogo (Journal of Global Pharma Technology, 2017)
Introduction. Osteomyelitis management with debridement, guttering, and systemic antibiotics often do not give satisfactory results due to the inability of antibiotics to reach the infection site. Another method of antibiotic delivery in the form of beads are deemed ineffective as it requires two separate surgeries. Combination of local antibiotics with absorbable porous hydroxyappetite scaffolding  and antibiotic carriers have not been studied. Methods. We conducted pre-test and post-test control group in a rabbit model of osteomyelitis. Ten rabbits divided in control group and the treatment group (n=5). We injected Staphylococcus aureus in the rabbit tibia, forming the osteomyelitis model, and subsequently performed treatment for osteomyelitis. In the control group, we performed debridement and administered ceftriaxone injection for 4 weeks, whereas in the treatment group, we added the combination of porous hydroxyapatite and gentamicin. Afterwards, we performed clinical assessment, x-ray examination, culture, and histopathology.Results. Radiologically, tibia cortical thickening scores improved in the treatment group compared to the control group (p=0.48) as well as histopathological osteomyelitis evaluation score (p=0,009). Clinically, there were improvements in the swelling scores (n=5) of the treatment group compared to control group, but no significant statistically (p=0.053). In culture, there were no significant difference between the two groups (p=1.00).Conclusion. Combination of porous hydroxyapatite and gentamicin as a local treatment of osteomyelitis of the rabbit tibia osteomyelitis models improved radiological and histopathological scores and also clinically compared to existing standard treatment procedures for chronic osteomyelitis